Improving safety in schools through solar-outdoor lighting application: a case study of school in Perak Tengah / Nur Azfahani Ahmad ... [et al.] - Ahmad, Nur Azfahani; Tun Jamil, Siti Jamiah; Samsul Rijal, Nurhidayah; Zawawi, Ahmad; Abd Ghani, Aida Affina (2022)
Within the past decades, solar lighting application has become a cost-effective solution for many outdoor lighting requirements. New inventions in solar panel technologies, light-emitting diode (LED) and batteries have made it possible for many schools, especially in rural areas to significantly increase safety aspects and eliminate the electricity bills associated with outdoor lighting. Solar-outdoor lighting can provide high-quality lighting for more than 3 days and will provide illumination for areas that have limited access to grid-electricity supply, especially in remote and rural areas, whilst promoting safety awareness. Many studies have proven that with the occurrence of brightness at the external facade of a building, it will increase the safety level and avoid crime. Therefore, this paper tries explored on the potential of applying solar-outdoor lighting in order to improve the safety level of rural schools in Perak. A case study has been selected in the central Perak through a community-based approach project. It involves a practical application for the case study in order to identify suitable system requirements of the technologies in improving safety for the schools that have limited lighting due to financial constraints. It is found that, after the installation of these solar-outdoor lightings, this school managed to improve between 50% to 80% illuminance uniformity ratio around the schools especially at secluded areas.